2015
DOI: 10.1123/ijspp.2014-0003
|View full text |Cite
|
Sign up to set email alerts
|

Lower-Leg Compression, Running Mechanics, and Economy in Trained Distance Runners

Abstract: The efficacy of and mechanisms behind the widespread use of lower-leg compression as an ergogenic aid to improve running performance are unknown. The purpose of this study was to examine whether wearing graduated lower-leg compression sleeves during exercise evokes changes in running economy (RE), perhaps due to altered gait mechanics. Sixteen highly trained male distance runners completed 2 separate RE tests during a single laboratory session, including a randomized-treatment trial of graduated calf-compressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 22 publications
1
49
0
1
Order By: Relevance
“…Furthermore, running economy during exercise did not differ significantly among the groups in the present study. Bringard et al ( 2005 ) demonstrated that application of compression tights improved economy of oxygen uptake (decreased slow component of O 2 elevation) during submaximal running, although the finding was not consistent with other studies (Ali et al, 2010 ; Sperlich et al, 2010 , 2011 ; Stickford et al, 2015 ). Born et al ( 2013 ) reported that the lack of an effect on physiological variables may be due to insufficient or inappropriate pressure intensities applied by compression garments.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Furthermore, running economy during exercise did not differ significantly among the groups in the present study. Bringard et al ( 2005 ) demonstrated that application of compression tights improved economy of oxygen uptake (decreased slow component of O 2 elevation) during submaximal running, although the finding was not consistent with other studies (Ali et al, 2010 ; Sperlich et al, 2010 , 2011 ; Stickford et al, 2015 ). Born et al ( 2013 ) reported that the lack of an effect on physiological variables may be due to insufficient or inappropriate pressure intensities applied by compression garments.…”
Section: Discussionmentioning
confidence: 87%
“…Pressure applied to large working muscles would also be crucial for reducing muscle oscillation. In contrast, an increasing number of studies have examined the benefits of partial-body-coverage compression garments (thigh length or knee length; Ali et al, 2010 , 2011 ; Barwood et al, 2013 ; Rugg and Sternlicht, 2013 ; Del Coso et al, 2014 ; Stickford et al, 2015 ), and no consensus on the efficacy of the garments on performance is available. Therefore, it is important to determine the optimal compressed area preventing a performance decrease during prolonged running.…”
Section: Introductionmentioning
confidence: 99%
“…Positive effects in performance have also been noted in incremental tests (Kemmler et al, 2009; Sear et al, 2010), repeated sprinting (Higgins et al, 2009; Born et al, 2014), and jumping height following submaximal exercise (Rugg and Sternlicht, 2013; Bieuzen et al, 2014) or after a 10 km run (Ali et al, 2011). Conversely, other studies have reported no measurable effect on limb volume (Areces et al, 2015), fractional oxygen utilization (Kemmler et al, 2009; Wahl et al, 2011; Born et al, 2014; Priego Quesada et al, 2015; Stickford et al, 2015), muscle oxygenation or blood flow (Vercruyssen et al, 2012; Born et al, 2014), heart rate or indicators of central cardiovascular adaptations (Ali et al, 2007; Sperlich et al, 2011; Wahl et al, 2011; Vercruyssen et al, 2012; Born et al, 2014; Priego Quesada et al, 2015), lactate or exercise metabolite removal (Kemmler et al, 2009; Ali et al, 2010; Sperlich et al, 2011; Wahl et al, 2011; Vercruyssen et al, 2012; Areces et al, 2015), ratings of perceived exertion (RPE) or DOMS (Ali et al, 2007, 2010; Bovenschen et al, 2013; Areces et al, 2015; Priego Quesada et al, 2015), running economy and gait kinematics (Varela-Sanz et al, 2011; Stickford et al, 2015; Vercruyssen et al, 2016), maximal voluntary and evoked contractions (Vercruyssen et al, 2016), as well as performance in repeated sprinting (Duffield et al, 2008), or in running performed at maximal (Ali et al, 2007; Priego Quesada et al, 2015) and at sub-maximal exercise intensities (Ali et al, 2007, 2011; Wahl et al, 2011; Vercruyssen et al, 2012; Priego Quesada et al, 2015). This abundant but heterogeneous literature may underline probable task-dependent ergogenic effects of the compression when used during exercise.…”
Section: Introductionmentioning
confidence: 93%
“…For swimming, sensor placement at the trunk/limbs/head was used to provide either arm strokes (for front crawl [ 63 , 80 , 107 , 110 , 263 ]), kick strokes (for front crawl [ 124 , 126 ] and freestyle [ 125 ]), or generic strokes (for front crawl [ 24 , 68 , 85 , 108 , 156 , 164 , 168 , 263 , 323 , 332 ], butterfly [ 24 , 68 , 85 , 156 ], breaststroke [ 24 , 68 , 85 , 164 , 291 ]). Stride and step frequency/duration have been assessed during running [ 153 , 157 , 160 , 162 , 174 , 191 , 202 , 204 , 229 , 230 , 242 , 243 , 262 , 294 , 295 , 302 , 321 , 327 ], skating [ 293 ], and in the run up of cricket ball delivery [ 264 ]. Revolution rate was characterised for ...…”
Section: Trendsmentioning
confidence: 99%
“…Revolution rate was characterised for a bowling ball [ 180 ] and during cycling [ 302 , 313 ]. Phase segmentation was performed in swimming (to identify front crawl stroke phases [ 80 , 164 , 246 , 247 ]), in cross-country skiing [ 120 , 207 , 237 ] and uphill mountaineering [ 121 ] (to determine cycle rate from plant and lift-off of each ski and pole ground contact), in ice hockey skating (to determine cycle rate from initial contact to blade-off for each skate [ 293 ]), and during running on a track (trunk placement [ 61 , 149 , 153 , 194 ] and shank or foot placement [ 140 , 209 , 295 ]), on a treadmill (trunk placement [ 77 , 203 , 315 , 320 ] and shank or foot placement [ 87 , 140 , 148 , 222 , 229 , 230 , 294 , 318 ]), and during the acceleration/maintenance phase of sprint running (trunk placement [ 70 ] and foot placement [ 57 ]).…”
Section: Trendsmentioning
confidence: 99%